Effects of Angiotensin Receptor Blockers (ARBs) on In-Hospital Outcomes of Patients With Hypertension and Confirmed or Clinically Suspected COVID-19. (12th September 2020) - Soleimani, Abbas; Kazemian, Sina; Karbalai Saleh, Shahrokh; Aminorroaya, Arya; Shajari, Zahra; Hadadi, Azar; Talebpour, Mohammad; Sadeghian, Hakimeh; Payandemehr, Pooya; Sotoodehnia, Mehran; Bahreini, Maryam; Najmeddin, Farhad; et al.
Abstract: BACKGROUND: There is an ongoing controversy about harms and benefits of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) in hypertensive patients with coronavirus disease 2019 (COVID-19). Given the unresolved debate, we investigated the association of ARBs with in-hospital outcomes of these patients. METHODS: In this retrospective observational study, we studied patients with COVID-19 who referred to Sina Hospital in Tehran, Iran, from 20 February to 29 May 2020. Patients with either positive real-time reverse-transcriptase polymerase-chain-reaction test of swab specimens, or high clinical suspicion according to the World Health Organization's interim guidance were included. We followed-up patients for incurring death, severe COVID-19, and in-hospital complications. RESULTS: We evaluated 681 patients with COVID-19 of whom 37 patients were excluded due to incomplete medical records and 8 patients who used ACEIs which left 636 patients in the analysis. In this cohort, 108 (17.0%) patients expired and 407 (64.0%) patients incurred severe COVID-19. Of 254 (39.9%) patients with hypertension, 122 (48.0%) patients were receiving an ARB. After adjustment for possible confounders, we found no independent association between taking ARBs and in-hospital outcomes except for acute kidney injury (AKI), in patients with confirmed or clinically suspected COVID-19, either hypertensive or not-hypertensive. We found that discontinuation of ARBs during hospitalization was associated with a greater risk of mortality, invasive ventilation, and AKI (all P ˂ 0.002). CONCLUSIONS: We found that taking ARBs by patients with hypertension and confirmed or clinically suspected COVID-19 is not associated with poorer in-hospital outcomes after adjustment for possible confounders.